Argentina : Insolvency and Creditor Rights Systems - World Bank (Washington, DC, 2013)
In 1995, Argentina enacted a new modern insolvency law that substantially improved corporate liquidations and rehabilitations. After almost seven years of experience, some legal and institutional weaknesses persist: (1) corporate workouts are difficult in practice; (2) the unified insolvency regime causes severe problems in judicial interpretation of many legal provisions, causing court congestion with insolvency cases; (3) an uneven playing field discourages rehabilitation; (4) a lack of insolvency specialization among judges impedes efficiency and uniformity in large commercial centers; and (5) sindicos are perceived as lacking objectivity and sufficient expertise to manage complex restructurings. Liquidation proceedings take 1-5 years (depending on complexity), while reorganizations average 1½-2 years in jurisdictions with specialized judges (Mendoza, Cordoba) and 2-3 years in the others. To immediately improve the system, a new workout mechanism should be introduced to deal with systemic levels of corporate distress. In the medium term, other aspects of the legal and institutional framework should be improved.